2016
DOI: 10.1105/tpc.15.00781
|View full text |Cite
|
Sign up to set email alerts
|

The Opposing Actions of Arabidopsis CHROMOSOME TRANSMISSION FIDELITY7 and WINGS APART-LIKE1 and 2 Differ in Mitotic and Meiotic Cells

Abstract: Sister chromatid cohesion, which is mediated by the cohesin complex, is essential for the proper segregation of chromosomes during mitosis and meiosis. Stable binding of cohesin with chromosomes is regulated in part by the opposing actions of CTF7 (CHROMOSOME TRANSMISSION FIDELITY7) and WAPL (WINGS APART-LIKE). In this study, we characterized the interaction between Arabidopsis thaliana CTF7 and WAPL by conducting a detailed analysis of wapl1-1 wapl2 ctf7 plants. ctf7 plants exhibit major defects in vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Immunolocalization of SYN1 in meiocytes confirmed that the release of cohesin during diakinesis is recovered in wapl1 wapl2 ctf7 triple homozygous mutant plants ( De et al, 2016 ). However, comet assay experiments in vegetative tissues revealed that both WAPL1/2 and ECO1/CTF7 are important for the repair of DNA DSBs during the cell cycle in Arabidopsis ( De et al, 2016 ). In addition, flow cytometry revealed a high level of aneuploidy in vegetative tissues of the triple mutant ( De et al, 2016 ).…”
Section: Cohesion Establishment and Maintenancementioning
confidence: 72%
See 4 more Smart Citations
“…Immunolocalization of SYN1 in meiocytes confirmed that the release of cohesin during diakinesis is recovered in wapl1 wapl2 ctf7 triple homozygous mutant plants ( De et al, 2016 ). However, comet assay experiments in vegetative tissues revealed that both WAPL1/2 and ECO1/CTF7 are important for the repair of DNA DSBs during the cell cycle in Arabidopsis ( De et al, 2016 ). In addition, flow cytometry revealed a high level of aneuploidy in vegetative tissues of the triple mutant ( De et al, 2016 ).…”
Section: Cohesion Establishment and Maintenancementioning
confidence: 72%
“…Hence, Arabidopsis WAPL genes may play a critical role during meiosis, and mechanisms involved in the removal of cohesin during prophase may vary between mitosis and meiosis in plants. Additionally, inactivation of the two Arabidopsis WAPL genes can suppress the lethal phenotype produced by the lack of CTF7 ( De et al, 2016 ) and allows for normal vegetative growth and production of a reduced number of viable seeds ( De et al, 2016 ). Immunolocalization of SYN1 in meiocytes confirmed that the release of cohesin during diakinesis is recovered in wapl1 wapl2 ctf7 triple homozygous mutant plants ( De et al, 2016 ).…”
Section: Cohesion Establishment and Maintenancementioning
confidence: 99%
See 3 more Smart Citations